Skills Of An Effective Communicator - Kovalik, M. David (Forum Manajemen; Vol 12 No 67 (1998): Forum Manajemen Prasetiya Mulya | Desember 1998- Januari 1999, 1998)
Since English has been labeled the universal business language, the majority of companies and corporations view English proficiency as an important prerequisite when recruiting potential employees.